The effect of intravenous neem's (Azadirachta indica A. Juss) seed oil on Plasmodium berghei in mice - Budi Mulyaningsih Budi Mulyaningsih (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2001)
Background: Malaria is one of the most important public health problems in the tropical countries such a Indonesia. Several actions have been taken to overcome this problem, however, its prevalence is still high. Vector resistance to insecticide and parasite resistance to drug were two of the major constraints in dealing with malaria. Therefore, alternative methods to control malaria which are effective and safe are needed.Objectives: To detect the effect of neem's (Azadirachta indica A. Juss) seed oil on Plasmodium berghei administered intravenously in mice.Methods: Seventy five Swiss mice were divided into 7 groups and each group was treated intravenously with 50 mg/KgBW, 100 mg/KgBW, 200 mg/KgBW, 400 mg/KgBW, 500 mg/KgBW neem's seed oil; 5 mg/KgBW chloroquine and 50 ml physiological salt respectively for a period of 4 days after infection. The blood samples were collected every day (D.,0 to D.3) from all experimental animals and the parasitemia were examined with Giemsa staining.Results: Effective dose (ED50) of neem's (Azadirachta indica A. Juss) seed oil on Plasmodium berghei in mice administered intravenously was 144.12 mg/Kg BW, and the inhibition effect of the dose of 800 mg/ KgBW was 78.61%.Conclusion: The neem's (Azadirachta indica A. Juss) seed oil on Plasmodium berghei administered intravenously in mice (800 mg/KgBW) has a potential inhibition effect on development of P. berghei.Keywords: Plasmodium berghei - Azadirachta indica A. Juss - effective dose - parasitemia - resistance